2005
DOI: 10.1159/000087212
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Study of Ferumoxytol: A New Iron Replacement Therapy in Normal Subjects and Hemodialysis Patients

Abstract: Background: Currently available intravenous iron preparations are not ideal, either because of safety concerns or dose limitations. We investigated the safety and pharmacokinetics of ferumoxytol, a new iron replacement therapy, in normal subjects and hemodialysis patients. Methods: In a randomized, double-blind, ascending-dose study in normal volunteers (n = 41), 6 subjects received placebo, and 8 subjects each received ferumoxytol, at 1, 2 or 4 mg iron/kg, injected at 60 mg iron/min. The remaining subjects re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 68 publications
4
87
0
Order By: Relevance
“…In plasma, the elimination half-life of FMX was 22.1 hours (n ¼ 14; 95% CI, 19.7-24.5; Fig. 3C), consistent with previously published data in healthy subjects (36,37) and comparable with the reported half-life of nal-IRI (11,35). Plasma exposure (AUC 0!t ) for FMX and nal-IRI were correlated (r ¼ 0.7528; P ¼ 0.0030).…”
Section: Fmx-mri Imaging and Quantitationsupporting
confidence: 91%
See 2 more Smart Citations
“…In plasma, the elimination half-life of FMX was 22.1 hours (n ¼ 14; 95% CI, 19.7-24.5; Fig. 3C), consistent with previously published data in healthy subjects (36,37) and comparable with the reported half-life of nal-IRI (11,35). Plasma exposure (AUC 0!t ) for FMX and nal-IRI were correlated (r ¼ 0.7528; P ¼ 0.0030).…”
Section: Fmx-mri Imaging and Quantitationsupporting
confidence: 91%
“…Other pharmacokinetic parameters for FMX are summarized in Supplementary Table S2. Metabolic turnover of FMX resulted in elevated plasma ferritin levels as described previously (29,36). Ferritin levels in plasma increased from a median concentration of 267 ng/mL (range, 45-1,481 ng/mL) during patient screening to 691 ng/mL (range, 430-1,730 ng/mL) at day 4 after FMX injection.…”
Section: Fmx-mri Imaging and Quantitationsupporting
confidence: 73%
See 1 more Smart Citation
“…The iron is then released intracellularly within vesicles in macrophages where it can bind to ferritin or incorporate into hemoglobin. (20) Although the physical, pharmacokinetic, and biologic properties of ferumoxytol in therapeutic trials have been reported for IV injection, (21) the authors are not aware of physicochemical characterization conducted on nebulized Rienso.…”
Section: Introductionmentioning
confidence: 99%
“…The blood half-life is dose-dependent and is approximately 14.5 hours at a dose of 4 mg/kg. 7 All subjects received ferumoxytol intravenously at a dose of 4 mg/kg (group A, n=12) or 6 mg/kg (group B, n=12) to a maximum dose of 510 mg of elemental iron.…”
Section: Materials and Methods Populationmentioning
confidence: 99%